Health Promotion Potential of Vegetables Cultivated in Northern Thailand: A Preliminary Screening of Tannin and Flavonoid Contents, 5α-Reductase Inhibition, Astringent Activity, and Antioxidant Activities - Naphatsorn Kumar PhD; Chaiyavat Chaiyasut PhD (SAGE Publishing, 2017)
Many of scientific evidences suggest that regular consumption of fruits and vegetables can prevent chronic diseases. In Northern Thailand, there are many vegetables that are usually consumed by local people. In this study, 17 local vegetables were selected and extracted with 95% ethanol. The extracts were screened for 5α-reductase inhibitory activity, total tannin and flavonoid contents, astringent and antioxidant activities. The results showed that Spondias pinnata and Ocimum americanum had the highest tannin and flavonoid content, respectively. Neptunia oleracea was the most potent 5α-reductase inhibitor. For antioxidant activities, S pinnata was the most potent ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) radical scavenger and the most potent ferric reducer. Polygonatum odoratum was the most potent hydrogen peroxide scavenger and Leucaena leucocephala was the most potent DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenger among the tested samples. This suggests that local vegetables in Northern Thailand have a health promotion potential, which can be further developed as nutritional supplements, preventive medicines, and topical products for cosmetic purposes.